1980
DOI: 10.1017/s0022112080000407
|View full text |Cite
|
Sign up to set email alerts
|

Shelves and the Korteweg-de Vries equation

Abstract: An extension of the analytical results of Kaup & Newell (1978) concerning the effect of a perturbation on a solitary wave of the Korteweg–de Vries equation is given and numerical studies are conducted to verify the conclusions. In all cases, the numerical results agree with the results predicted by the theory. The most striking feature of the perturbed flow is the presence of a shelf in the lee of the solitary wave whose role is to absorb (provide) the extra mass which is created (depleted) by the perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 9 publications
0
64
0
Order By: Relevance
“…Thus, our problem is now broken into two regions: the region that matches imposed non-decaying boundary condition behaviour at infinity that is unaffected by the soliton, and the region in which the O(e) correction term is valid and the solution is quasi-stationary. We introduce a boundary layer in which there is a transition from the non-zero value in the perturbation term to the boundary conditions at infinity (see also Knickerbocker & Newell 1980;Kodama & Ablowitz 1981). Note in this section we will consider the more general case when u ∞ is a function of Z = ez.…”
Section: Boundary Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our problem is now broken into two regions: the region that matches imposed non-decaying boundary condition behaviour at infinity that is unaffected by the soliton, and the region in which the O(e) correction term is valid and the solution is quasi-stationary. We introduce a boundary layer in which there is a transition from the non-zero value in the perturbation term to the boundary conditions at infinity (see also Knickerbocker & Newell 1980;Kodama & Ablowitz 1981). Note in this section we will consider the more general case when u ∞ is a function of Z = ez.…”
Section: Boundary Layermentioning
confidence: 99%
“…They were needed to effectively understand the KdV equation under perturbation (cf. Knickerbocker & Newell 1980;Ablowitz & Segur 1981). In the KdV equation, there is a small shelf produced in the wake of the soliton.…”
mentioning
confidence: 99%
“…In the region 0 < 0 < 6 c (x) the amplitude of the shelf is small (that is, O(n)) and varies slowly with respect to the variables T and 6 (that is, the z and 6 derivatives are O(p)) (24,25,26). Thus, in this slowly-varying small-amplitude shelf region the evolution of the tail will be described by an asymptotic expansion of the form…”
Section: Shelf Emergence and Subsequent Evolutionmentioning
confidence: 99%
“…The shelf represents a small-amplitude (on the order of the non-dimensional retardation time) dilation of the tube. The dilation extends from the decaying main pulse to the current position associated with a hypothetical Korteweg-Moens pulse (24,26). Beginning at the Korteweg-Moens phase position, the shelf undergoes a series of viscoelastically modified high-wavenumber oscillations (that is, a dissipative and dispersive wavetrain) in the transition to a zero-amplitude background state.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of plane solitary waves over variable depth is now well understood ( [3,14,10,11,7]). In this problem it is shown that, starting from an initial solitary-wave solution of the KdV equation ( [12]), the propagation over a region of varying depth introduces a shelf directly behind the primary wave, a left-going (reflected) 'shelf' and another right-going 'shelf' (re-reflection).…”
Section: Introductionmentioning
confidence: 99%